Building better barriers: how nutrition and undernutrition impact pediatric intestinal health - Andres, Sarah F.; Zhang, Yang; Kuhn, Madeline; Scottoline, Brian (Frontiers in Immunology, 2023)
Chronic undernutrition is a major cause of death for children under five, leaving survivors at risk for adverse long-term consequences. This review focuses on the role of nutrients in normal intestinal development and function, from the intestinal epithelium, to the closely-associated mucosal immune system and intestinal microbiota. We examine what is known about the impacts of undernutrition on intestinal physiology, with focus again on the same systems. We provide a discussion of existing animal models of undernutrition, and review the evidence demonstrating that correcting undernutrition alone does not fully ameliorate effects on intestinal function, the microbiome, or growth. We review efforts to treat undernutrition that incorporate data indicating that improved recovery is possible with interventions focused not only on delivery of sufficient energy, macronutrients, and micronutrients, but also on efforts to correct the abnormal intestinal microbiome that is a consequence of undernutrition. Understanding of the role of the intestinal microbiome in the undernourished state and correction of the phenotype is both complex and a subject that holds great potential to improve recovery. We conclude with critical unanswered questions in the field, including the need for greater mechanistic research, improved models for the impacts of undernourishment, and new interventions that incorporate recent research gains. This review highlights the importance of understanding the mechanistic effects of undernutrition on the intestinal ecosystem to better treat and improve long-term outcomes for survivors.